MEAN PERFORMANCE EVALUATION OF OKRA PARENTS AND CROSSES BASED ON MORPHOLOGICAL AND BIOCHEMICAL PARAMETERS - KHAN, F; SAEED, A; FATIMA, N; ULLAH, I; IQBAL, RA; KHAN, ZA; RABNAWAZ, .; TOOR, S; ARSHAD, M; SIDDIQ, MA; AHMAD, MI (Biological and Clinical Sciences Research Journal, 2024)
Okra is a traditional vegetable famous for its nutritional value. It is a perfect villager’s vegetable due to its robust nature, dietary fiber, and seed protein balance of both tryptophan and lysine. The research was carried out in the research area of the Department of Plant Breeding and Genetics, University of Agriculture Faisalabad. Cross combinations among 3 lines (Patel, Selection Super Green, and 19234) and 3 testers (IQRA-III, Perbhani Karanti, and Sabz Pari) were developed by using line × tester design. Crossed seeds along with parents were grown in the field under Randomized Complete Block Design (RCBD) with three replications. Data for various morphological traits i.e. plant height, pod length, number of fruits, number of ridges per pod, fruit diameter, fresh fruit weight, number of fruit-bearing nodes, leaf length, and leaf breadth was collected and analyzed statistically through analysis of variance and used to assess mean performance. Correlation analysis was also performed for various plant traits to check the association of characters. Characters’ plant height, fruit length, fruit weight, leaf length, and ADF are significantly associated with the number of fruits at the genotypic level. Fruit length exhibited a significant positive association with plant height, fruit weight, and number of fruits at the genotypic level.